Pemanfaatan Media Sosial Instagram Sebagai Media Komunikasi Pemasaran Pada Event Thrifting Nglapak Day - Firmandika, Rifky Wananda; Riyanto, Buddy; Astuti Itasari, Andri (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Utilizing social media as a marketing communications medium has become a popular strategy. This is due to the ability of social media to reach a wide audience at a relatively low cost, as well as its ability to build deeper interaction and engagement with the audience, as is done by Instagram Nglapak Day. The aim of this research is to find out how to optimize media Instagram social as a marketing communication medium at the Nglapak Day thrifting event. In this research, researchers used qualitative methods. The collected data was then analyzed using the Miles and Huberman data analysis model. The problem with Nglapak Day is that it does not optimize the use of Instagram as a marketing communications medium. The results of this research are alternative suggestions given to Nglapak Day for optimizing Instagram social media as a marketing communications medium which is supported by the Circular Model of SoMe theory according to Regina Luttrell in her book Social Media: How to Engage, Share, and Connect.